Observable protective activities of quercetin on aluminum chloride-induced testicular toxicity in adult male Wistar Rat - John Afees Olanrewaju; Toluwani Gabriel Akinpade; Sunday Yinka Olatunji; Joshua Oladele Owolabi; Joseph Igbo Enya; Stephen Taiye Adelodun; Sunday Oluseyi Fabiyi; Ayodele Babajide Desalu (Wolters Kluwer Medknow Publications, 2021)
Background: Aluminum chloride (AlCl3 ) present in many manufactured consumable is considered as a toxic element. Aim: Our study evaluates the toxic effects induced by AlCl3 on the testes as well as the therapeutic tendency of Quercetin (QUE) agent as an antioxidant. Setting and Design: In the department of Anatomy of Medical School. Methods and Materials: Thirty-two male Wistar rats weighing approximately 170 ± 10 g were assigned into four groups with eight each, fed with rat chow and water ad-libitum. Group A served as control and was given distilled water throughout; Group B was given only QUE (200 mg/kg body weight) for 21 days; Group C was given only AlCl3 (300 mg/kg body weight) for 14 days; and Group D was given AlCl3 (300 mg/kg body weight) for 14 days followed with QUE (200 mg/kg body weight) for 21 days. Substance administrations were done orally. Statistical analysis: One-way analysis of variance was used to analyze the data, in GraphPad Prism 6.0 being the statistical software. Results: AlCl3 significantly reduced the relative organ (testes) weight, correlating the decrease in sperm count, sperm motility and sperm viability. Furthermore, there was a decrease in luteinizing hormone with an increase in follicle-stimulating hormone which accounted for a significant reduction in testosterone level that plays a great role in spermatogenesis, following AlCl3 treatment. The cytoarchitecture of the testes showed degenerative changes in the seminiferous tubules and leydin cells, nitric oxide synthases immunoreactivity was intense in the seminiferous epithelium of rat in Group C. Conclusion: These suggest that QUE antioxidant property could reverse the decrease in sperm status, hormonal effects, and functional deficit induced by aluminum chloride on the testes of Wistar rats.